Late-onset spondyloarthritis in a Colombian population: findings from the GESPA cohort (2026)
Background: Spondyloarthritis (SpA) comprises a heterogeneous group of inflammatory diseases with axial and/or peripheral involvement and typically presents in young men. However, a less recognized subgroup presents with onset disease after 45 years of age, referred to as late-onset spondyloarthritis (LO-SpA), which appears to differ phenotypically from the classical pattern of presentation. Objective: To characterize the clinical, serological, and imaging features LO-SpA in a Colombian cohort and to compare them with those of early-onset spondyloarthritis (EO-SpA). Methods: An analytical cross-sectional study was conducted including 496 patients from the GESPA registry of Hospital Militar Central–Universidad de La Sabana (1990-2025). Adults aged =18 years with a confirmed diagnosis of SpA by expert rheumatologists were included. Clinical characteristics, medical history, laboratory data and imaging findings were collected. Patients with symptom onset after 45 years of age were classified as having LO-SpA. Clinical, laboratory, and imaging characteristics were compared between LO-SpA and EO-SpA groups and factors associated with LO-SpA were analyzed using logistic regression.